PENGARUH PROFESIONALISME DAN KOMPETENSI PEGAWAI TERHADAP KUALITAS LAPORAN KEUANGAN - Fariz Mustaqim; La Ode Abdul Rakhman; Ahmad Daholu (AT TARIIZ : Jurnal Ekonomi dan Bisnis Islam, 2025)
This study aims to examine the effect of professionalism and employee competence on the quality of financial statements in the Central Buton Regency Government. The research employs a quantitative approach using multiple linear regression analysis to identify the relationships among variables. Data were collected through questionnaires distributed to respondents directly involved in the preparation of financial statements and were subsequently analyzed using SPSS software. The results of the analysis indicate that professionalism has a positive and significant contribution to improving the quality of financial statements, as evidenced by a t-test significance value of 0.001 and a regression coefficient of 0.232. Employee competence is also proven to have a positive and significant effect, with a significance value of 0.000 and a regression coefficient of 0.267. Simultaneously, both independent variables demonstrate a significant effect on the quality of financial statements, as indicated by an F-test significance value of 0.000.